Presenting a Model of Implementing Process of Public Administration Approach in Development Programs in Iran, Using a Mixed Methods Research Strategy - Hadi Mohammadzadeh Soltanmoradi; Tahereh Feizy; Masoud Geramipour; Mehdi Yadollahi (مدیریت دولتی, 2021)
Objective: The purpose of this study is to illustrate the process of applying the “new public management” approach in the country, explain the approach that has been implemented in practice and compare it with the claimed approach. Methods: In this research, a mixed-methods research design has been used. In the qualitative stage, the strategy of grounded theory (Strauss and Corbin’s systematic design) and the theoretical sampling method have been used. In a quantitative stage, a survey and correlation strategy was used and 400 people were selected as a sample using the multistage random sampling method. To estimate the parameters and perform structural equation modeling, the maximum likelihood method has been used in Amos 24 software.Results: The results of research in both qualitative and quantitative sections show that imitation and convergence with the global trend are the main factors in choosing the "new public management" approach. The results also show the weak effect of choosing the "new public management" approach and the relatively strong effect of specific conditions on increasing the inefficiency of the current management approach of the country. The choice of the "new public management" approach in the country, along with the specific conditions of the management system, has led to greater inefficiency and increased negative consequences.Conclusion: In a general conclusion, it can be said that improving the three important components of good governance, namely the rule of law, transparency and control of corruption are the main prerequisites for applying the “new public management” approach and its main pillar, namely privatization. Otherwise, applying this approach in the public sector will have much more negative consequences.